2018
DOI: 10.1093/nar/gky1147
|View full text |Cite
|
Sign up to set email alerts
|

Splicing of long non-coding RNAs primarily depends on polypyrimidine tract and 5′ splice-site sequences due to weak interactions with SR proteins

Abstract: Many nascent long non-coding RNAs (lncRNAs) undergo the same maturation steps as pre-mRNAs of protein-coding genes (PCGs), but they are often poorly spliced. To identify the underlying mechanisms for this phenomenon, we searched for putative splicing inhibitory sequences using the ncRNA-a2 as a model. Genome-wide analyses of intergenic lncRNAs (lincRNAs) revealed that lincRNA splicing efficiency positively correlates with 5′ss strength while no such correlation was identified for PCGs. In addition, efficiently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 95 publications
1
46
0
Order By: Relevance
“…Pir2 and cryptic intron-based mechanisms repress targets throughout the genome and may be conserved in higher eukaryotes. Indeed, we note that ARS2 interacts with splicing factors in human cells, and lncRNAs such as XIST implicated in X-chromosome inactivation contain inefficiently spliced introns 47,48 . Considering that defects in lncRNAmediated gene regulation contribute to human diseases including cancer and that ARS2 is commonly mutated in various types of cancer, our findings may shed light on pathways contributing to the misexpression of genes, ultimately leading to the development of specific therapeutic strategies.…”
Section: Discussionmentioning
confidence: 91%
“…Pir2 and cryptic intron-based mechanisms repress targets throughout the genome and may be conserved in higher eukaryotes. Indeed, we note that ARS2 interacts with splicing factors in human cells, and lncRNAs such as XIST implicated in X-chromosome inactivation contain inefficiently spliced introns 47,48 . Considering that defects in lncRNAmediated gene regulation contribute to human diseases including cancer and that ARS2 is commonly mutated in various types of cancer, our findings may shed light on pathways contributing to the misexpression of genes, ultimately leading to the development of specific therapeutic strategies.…”
Section: Discussionmentioning
confidence: 91%
“…7c). Second, we inspected binding of RBPs to their own NMD transcripts using available eCLIP and iCLIP data [39][40][41] . In several cases, such as BCLAF1, TIAL1, SRSF5, SRSF6 and HNRNPL, a conserved PCE that generates Split-ORFs was massively bound by the encoded RBP (Fig.…”
Section: Rna Binding and Oligomerization Of Srsf7 Drive The Formationmentioning
confidence: 99%
“…Despite evidence that the functions of most elincRNAs is likely transcription dependent, a relatively large proportion of eli-ncRNAs is not only stably transcribed but also undergoes splicing (Marques et al, 2013;Hon et al, 2017;Krchnakova et al, 2019). Recently, splicing of Blustr, a lincRNA expressed in mouse embryonic stem cells (mESCs) whose transcriptional start site initiates from an active enhancer (Mouse ENCODE Consortium et al, 2012), was shown to be sufficient to modulate the expression of its cognate protein-coding gene target in cis (Engreitz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%